Preobrazba pokrajine na Bovškem v zadnjih dveh stoletjih - Eniko, Urška (Geografski obzornik, 2000)
The article presents some changes in Bovško, the mountainous landscape in the northwestern Slovenia, in the last two hundred years. It is mainly based upon the analysis of Josephinian military map from the second half of the 18th century, Franciscan cadastral register from the first half of the 19th century, present maps and field work.
Keywords: Bovško; družbena geografija; kulturna krajina; naselja; Posočje; Slovenija; spremembe; zgodovinski pregledi